1987
DOI: 10.1148/radiology.163.1.3823455
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer and gastric carcinoma: diagnosis with biphasic radiography compared with fiberoptic endoscopy.

Abstract: The diagnostic value of biphasic radiographic examination of the stomach and duodenum was compared with that of fiberoptic endoscopy in a prospective, blinded study of 385 patients with dyspepsia. This investigation was directed at gastric malignancies and peptic ulcers. Methodologically there is no absolute standard for a study of this kind because histologic examination is useful for detection of cancer but inadequate for ulcers. As an alternative, kappa indexes and the sensitivity and specificity, as derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Precise preoperative evaluation of the depth and size of early gastric carcinoma should be performed by radiology, endoscopy with biopsy, and EUS. In a prospective, blind comparison, Shaw et al15 found that double‐contrast radiography and endoscopy were equally capable of detecting early gastric carcinoma. Tumor depth (mucosa or submucosa) was diagnosed accurately by EUS in 55% of our patients and in 72% of patients reported by Sano et al16 Overdiagnosis of tumor depth may be related to submucosal fibrosis and disorganized muscularis mucosae caused by the ulceration of the tumor per se or a previous endoscopic biopsy,17 the distinction of which occasionally may be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Precise preoperative evaluation of the depth and size of early gastric carcinoma should be performed by radiology, endoscopy with biopsy, and EUS. In a prospective, blind comparison, Shaw et al15 found that double‐contrast radiography and endoscopy were equally capable of detecting early gastric carcinoma. Tumor depth (mucosa or submucosa) was diagnosed accurately by EUS in 55% of our patients and in 72% of patients reported by Sano et al16 Overdiagnosis of tumor depth may be related to submucosal fibrosis and disorganized muscularis mucosae caused by the ulceration of the tumor per se or a previous endoscopic biopsy,17 the distinction of which occasionally may be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, this resource is not available to the same extent in all geographic areas and consequently, primary care physicians often use upper gastrointestinal series, which are less expensive and easily accessible. However, radiography has consistently been shown to provide inferior diagnostic accuracy in detecting structural causes of dyspepsia (66,67). In order to decrease the risk of wrong diagnosis with upper gastrointestinal series, a process of matching a carefully established clinical diagnosis and a radiographic report should lead the physician to pursue the investigation with endoscopy each time that there is discordance.…”
Section: Ascertain When Appropriate That the Upper Gastrointestinalmentioning
confidence: 99%
“…Double contrast gastrography has comparable sensitivity to endoscopy for the detection of gastric ulcers in man. 66 Nuclear scintigraphy is particularly applicable to the evaluation of gastric motility, since quantitative assessments of gastroesophageal reflux and gastric emptying rate can be made. The principal disadvantage of gastric scintigraphy is the poor anatomic detail of the images.…”
Section: Stomachmentioning
confidence: 99%